Draft National Health Policy 2000 - Qadeer, Imrana; Davar, Bhargavi V.; Duggal, Ravi (2002)
Had the new health policy document proposed an overarching vision of how all the elements it enumerates would be put in place, it would have been a visionary document. As it stands the draft policy is riddled with contradictions and confusions. It spells a significant departure from the 1983 policy objectives of providing primary health care for all, specially the underprivileged. Instead of creatively utilising private sector to provide basic affordable health care, it all but hands over the task to the private sector, inevitably undermining exising national health programmes. By encouraging the corporate involvement in tertiary and secondary level medical care without first ensuring their access to the underprivileged, the draft denies the rights of the poor to good care. - Reproduced.
Keywords: Health services - India; Health services